A practical approach in differentiating IBD from other causes of enterocolitis - Hilmi, Ida Normiha; Nik Muhamad Affendi, Nik Arsyad; Khoo, Xin hui; Nik Mustapha, nik raihan; Chia Hsin Chew, Deborah (Wiley, 2015)
Inflammatory bowel disease (IBD) is emerging in Asia, but there are many challenges in making the diagnosis. There is no gold standard for the diagnosis of IBD, which is often made based on a combination of clinical, endoscopic, radiological, and histologi- cal features, none of which are specific for the condition. Although there are many non- infectious mimics, such as Behcet's, drug-induced enterocolitis, and lymphoma, the main dilemma is differentiating IBD from infection; namely, Crohn's disease (CD) from intestinal tuberculosis (ITB). However, a careful history/examination, targeted investigations, along with histopathology should make it possible to make a definitive diagnosis of IBD in the majority of cases. In cases where the diagnosis is still unclear, empirical treatment based on the most likely diagnosis can be started, but careful reassessment is essential.